THEOLOGICAL PERSPECTIVE OF JABARIYAH THROUGH COGNITIVE PSYCHOLOGY AND DECISION-MAKING IMPLICATIONS - Ni'matul Maula (Makkah: Journal Of Islamic Studies, 2025)
Abstract: This study aims to examine Jabariyah theology through the framework of cognitive psychology and its impact on individual decision-making processes. Jabariyah theology asserts that all events occur solely by the absolute will of God, without human intervention, which has implications for the development of an external locus of control within the cognitive structure. This research employs a library research method, utilizing secondary data drawn from classical and contemporary literature, scholarly journals, academic articles, and scientific publications discussing the concept of Jabariyah and cognitive psychological theories. The analysis is conducted using a descriptive-qualitative approach to explore the relationship between theological doctrines and cognitive mechanisms in decision-making. The findings indicate that internalization of Jabariyah theology may lead to passive attitudes and a reliance on fate, which influence individual motivation and initiative in making decisions. However, variations in interpretation exist, with some individuals managing to integrate the Jabariyah concept with the principle of human effort (ikhtiar), thereby maintaining adaptive and dynamic decision-making. This study contributes to the interdisciplinary understanding between Islamic theology and cognitive psychology and opens opportunities for the development of new theories concerning the relationship between religious beliefs and human cognitive processes.